Interprofessionality in the model courses of study for healthcare and nursing professions in North Rhine-Westphalia, Germany / Interprofessionalität in den Modellstudiengängen der Pflege- und Gesundheitsberufe in Nordrhein-Westfalen - Hallwaß Anke; Hollweg Wibke (Sciendo, 2017)
Interprofessional cooperation is attributed a special significance in overcoming new challenges in the health system. For the educational system, this means the development of innovative teaching and learning formats that encourages interaction between students from different professions within healthcare. In Germany in the state of North Rhine-Westphalia (NRW), eleven model courses of study for healthcare and nursing professions have been developed and evaluated. Evaluation reports do not tell whether social interaction between students of different professions is promoted. The following study investigates to what extent interprofessionality is incorporated into the model courses of study for healthcare and nursing professions in NRW and to what extent the courses of study include social interaction between students of different professions. In addition, an analysis is made as to what extent structural and organisational conditions and the course management influence the (further) development of the courses with a view to interprofessionality. Structured expert interviews have been carried out with those responsible for the courses of study, for a total of seven model courses. These have then been evaluated using qualitative content analysis. The promotion of interprofessional expertise is incorporated into all model study courses that were considered and is generally governed by international standards. Six of the seven courses of study offer social interaction between students of different professions. Valuable hints for interprofessional education at colleges for health could be achieved.